Covid-19 as a Non-Military Threat - Predi Muliansyah (Resolusi: Jurnal Sosial Politik, 2021)
Indonesia is one of the countries affected by the Covid-19 pandemic and its spread is still ongoing. The Covid-19 pandemic has affected government policy making and services both at the central and regional levels. The government is required to continue to take various steps to adapt to developments caused by this pandemic. The purpose of this study includes the efforts of the Civil Servants as one of the elements of the National Defense Reserve Component in dealing with Covid-19 as a non-military threat. The method used in this research is qualitative with research design using literature study. The research data were taken from journals, books, previous research, scientific articles, literature and news from official websites and the research subject was the Civil Servants. The results of the research are that the Civil Servants as a government apparatus should be a pioneer and take part at the forefront of every effort to defend the country, according to their respective fields and responsibilities. In the implementation of defending the state in the daily work of the Civil Servants in the form of love for the homeland, being aware of the nation and state, namely Pancasila as the ideology of the State, willing to sacrifice for the nation and the State, having the initial ability to defend the State.